Comparison of Oral Hygiene Status among Right and Left-Handed Individuals - Aqsa Iqbal, Sana Masood, Ambrina Qureshi, Sadaf Arshi (Pakistan Journal of Medical & Health Sciences, 2023)
Objectives: To assess difference in oral hygiene status among right- and left-handed individuals using different dental indices. Materials and Methods: The research was conducted among two hundred and ninety-six students aged between 18 to 25 years. Data was collected using convenience sampling technique. Handedness was ascertained by using Edinburgh handed scale. Students were provided questionnaire to be filled about oral hygiene practices and oral examination was performed to assess DMFT, Plaque Index, Gingival Index and Oral Hygiene Index Simplified. Data was analyzed using SPSS software version 21. Results: The study showed that 16.2% of the participants were males and 83.8% were females. Out of these 90.55% were right-handed and 9.5% were left-handed. It was observed that scores of left-handed individuals were higher with mean DMFT score (0.06), OHI-S score (1.71) and PI score (1.11) when compared to right-handed people. However, greater GI score was seen in right-handed (0.44). Conclusion: This study concluded that individuals who are right-handed have better oral hygiene as seen by their better DMFT, OHI-S and PI scores and therefore lower frequency of dental caries. Practical implication: The difference in oral hygiene status among right- and left-handed highlights the need to focus on manual dexterity that effects brushing efficiency and ultimately oral hygiene performance. Keywords: Gingival health, Oral hygiene, Dental caries, Right- and Left-handedness, Manual dexterity